Motives for Using TikTok Social Media Application Among Students of SMAN 3 Mataram After the Covid-19 Pandemic - Irsyadusshahibul Fadhilah (Didaktika: Jurnal Kependidikan, 2024)
The rapid development of technology, especially the internet, has a major influence on changing people's lifestyles, one of which is in communication media. With the development of the internet in society, what is now called social media has emerged. In 2016, precisely in September, a social media application called TikTok. TikTok itself is a social media platform that allows its users to create short videos equipped with several features such as filters, music, and others. As time went by, TikTok regained popularity in early 2020, a time when the world was experiencing the Covid-19 pandemic. As of July 2023, Indonesia is the second largest user of the TikTok app in the world. Indonesia is ranked second with the highest number of TikTok users in the world, reaching 112.97 million users. The purpose of this research is to find motives that encourage the use of TikTok social media among students of SMAN 3 Mataram. This research was conducted using qualitative methods on 20 subjects. From the results of the study, it was found that the motives that encourage the use of TikTok social media among students of SMAN 3 Mataram are information motives, self-identity motives, social interaction motives, and entertainment motives. However, the four motives do not all appear in students; the motives that are often found are information motives and entertainment motives.